The evaluation of training courses for experienced agriculturalists - Girdler, Derek (1991)
An evaluation of the effectiveness of a training course is very difficult to implement, but it is necessary if the course is to achieve the objectives set out by the course designers. When the participants have completed their training, they should be equipped with the knowledge of the latest developments in their discipline, the skills to be able to put them into practice and the attitude to utilise this training experience to the full in the farm or unit situation. This study assesses the techniques available for evaluation and has selected one method of appraising Adult Short Courses, designed specifically for experienced agriculturalists from a particular farm discipline. The Agricultural Training Group Officer established the training needs of group members and organised a programme based at a central location and staffed by A. T. B. or external instructors. A questionnaire was administered to the population of course attenders at the end of each training day. The levels of knowledge, skills and attitudes were measured using a range of question designs and rating scales. The "before" level was valued at the same time as the "after" score. This is a departure from the more commonly used Pretest, Posttest design. Unit or farm physical performance data, related to stockperson control, was collected over the relevant years. A commercial psychological test was also used to evaluate the trainability of the course attenders. A comparative group of experienced agriculturalists, who were not involved in any A. T. B. training related to their unit attachment, were contacted to provide similar information and reduce any maturation, historical and local errors. The data collected showed significant increases in knowledge, skills and attitude levels with some degree of improvement in unit physical performance. The correlations between the objective criteria, unit physical data, and the subjective criteria, self-assessment ratings, were very mixed for the course attenders. The psychological tests tended to support independent unit manager valuations of the trainees. The training courses were effective and the evaluation has shown that trained staff can improve unit physical performance. The analysis supported the methodologies employed and further testing, with some modifications, using a larger population involved in a range of farm disciplines would be useful.